Análise eletromiográfica da função dos músculos do assoalho pélvico de gestantes - Moccellin, Ana Silvia (2014)
Introduction: During pregnancy, the mechanisms of pelvic organs support and continence maintenance may change, because the uterus progressive increase in mass and volume associated with fetal weight, or by hormonal changes. In this context parity and vaginal delivery are considered factors that may predispose to the development of pelvic floor muscles disorders, such as urinary incontinence, which can adversely affect the pregnant women quality of life. Thus, it becomes important to evaluate these muscles during pregnancy and among the used methods, there is the electromyography. However there are still evidence about pregnancy and delivery impact on pelvic floor muscles function during pregnancy. Objectives: We performed three studies in order to systematize and analyze the scientific evidence about the electromyographic evaluation of pelvic floor muscles function in pregnant women (STUDY I), to compare the pelvic floor muscles function in the third trimester between primigravid pregnant women and primiparous pregnant women who had previous vaginal delivery, identifying the factors that may predispose pregnant women to pelvic floor dysfunction (STUDY II), and to compare the quality of life of pregnant women with and without urinary incontinence, identifying the main factors that negatively affect quality of life (STUDY III). Methodology: The study I conducted a systematic review of electronic databases: Medline, PubMed, Scielo, Pedro and Lilacs until july/2013, searching studies that used protocols for evaluating the pelvic floor muscles function during pregnancy, by electromyography. Study II evaluated the pelvic floor muscles function of 19 primigravid pregnant women and 21 primiparous pregnant women who had previous vaginal delivery, between 34th and 36th gestational week, by surface electromyography, with the following protocol: 15 seconds of rest to basal activity registration, three maximal voluntary contractions held by two seconds, with an interval of one minute between each one, and three volunteers sustained contractions, held for six seconds, with an interval of one minute between each one. In study III were evaluated, in 24-28th and 34-36th gestational week, 15 pregnant women with urinary incontinence complaint and 25 pregnant women without urinary complaints, by the application of two quality of life questionnaires (King Health Questionnaire and World Health Organization Quality of Life). Data from studies II and III were tabulated in Excel and statistically analyzed with the Statistica 6.0 program. We adopted a significance level of 5 %. Results: The results of systematic review showed that pregnant women assessments occurred mainly in the 3rd trimester, using the vaginal probe, following protocols with one to three contractions, lasting two to 60 seconds, using the arithmetic mean of contraction amplitudes obtained in each assessment to electromyographic data analysis. The study II indicated there were no differences in pelvic floor muscles function, in the third trimester, between primigravid and primiparous pregnant women, but there was a significant increase in pregnant women BMI and a negative and significant correlation of baby weight variable with the peak electromyographic signal value during maximal voluntary contraction. Study III showed that pregnant women without urinary complaints had better quality of life than those with urinary complaints on the physical, social and environmental domains, and that pregnant women with urinary complaints had worse scores on the general health perception and impact of incontinence domains during the third trimester. Conclusions: Thus, this study revealed that the main factors that can change the electromyographic activity pattern of pelvic floor muscles during pregnancy, influencing their support and continence function, are those related to gestational process, such as increasing maternal body mass and baby weight. Furthermore, possible pelvic floor muscles dysfunction decreases pregnant women quality of life, which makes the pelvic floor muscles assessment important during pregnancy. However, there is no standardization between electromyographic evaluation protocols of pregnant women pelvic floor muscles function, available in literature.